Chemotherapy for pancreatic cancer - Springfeld, Christoph; Jäger, Dirk; Büchler, Markus W.; Strobel, Oliver; Hackert, Thilo; Palmer, Daniel H.; Neoptolemos, John P. (La presse médicale & Quarterly medical review, 2019)
Summary - Chemotherapy is an important part of multimodality pancreatic cancer treatment. After curative resection, adjuvant chemotherapy can significantly improve disease free survival and overall survival. The current standard of care is six months adjuvant chemotherapy with modified folinic acid, 5-fluorouracil, irinotecan and oxaliplatin (mFOLFIRINOX) in patients fit enough for this protocol, otherwise six months of gemcitabine and capecitabine based on the European Study Group for Pancreatic Cancer (ESPAC)-4 study. In patients with metastatic disease, combination chemotherapy according to the FOLFIRINOX protocol or with gemcitabine plus nab-paclitaxel is an important improvement to gemcitabine monotherapy that was the standard for many years. Patients not fit for combination chemotherapy however may still benefit from gemcitabine. Patients with good performance status may benefit from second-line chemotherapy. Chemoradiation has long been used in locally advanced pancreatic cancer but is now tempered following the LAP07 study. This trial showed no difference in overall survival in those patients with stable disease after four months of gemcitabine (with or without erlotinib) randomized to either continuation of gemcitabine therapy or chemoradiation (54Gy with capecitabine). As an alternative to radiation, other forms local therapies including radiofrequency ablation, irreversible electroporation, high-intensity focused ultrasound, microwave ablation and local anti-KRAS therapy (using siG12D-LODER) are currently under investigation. Given the systemic nature of pancreas cancer from an early stage, the success of any local approach other than complete surgical resection (with adjuvant systemic therapy) is likely to be very limited. In patients with locally advanced, irresectable cancer, chemotherapy may offer the chance for secondary resection with a survival similar to patients with primary resectable disease. Downstaging regimens need to be evaluated in prospective randomized trials in order to make firm recommendations. Selection of patient groups for specific therapy including cytotoxics is becoming a reality using assays based on drug cellular transport and metabolism, and molecular signatures. Going forward, high throughput screening of different chemotherapy agents using molecular signatures based on patients’ derived organoids holds considerable promise.